TRANSFORMATION OF LEGAL POLITICS IN INDONESIA FROM LIBERAL DEMOCRACY TO PANCASILA DEMOCRACY - Christianto , Christianto; Ismaidar , Ismaidar; Tamaulina Br. Sembiring (International Journal of Synergy in Law, Criminal, and Justice, 2025)
The transformation of legal politics from liberal democracy to Pancasila democracy is an important phenomenon in the history of the legal journey in Indonesia. This change reflects the nation's efforts to create a political and legal system that is in accordance with the personality, culture, and values ​​of Pancasila as the state ideology. During the liberal democracy era, law was oriented towards protecting individual rights and the supremacy of law with a legalistic approach. However, this system faced various obstacles, such as political instability, ideological polarization, and weak consistency in law enforcement. Through the Presidential Decree of July 5, 1959, Indonesia began the transition to Pancasila democracy, which emphasizes the values ​​of deliberation, mutual cooperation, and social justice. This transformation has major implications for legal politics, including a change in legal orientation from individualistic to collective and contextual. However, the implementation of Pancasila democracy is not free from challenges, such as the politicization of law, social inequality, and weak legal culture. This study uses normative methods with a legislative and historical approach to analyze changes in the legal system as well as challenges and opportunities in the implementation of Pancasila democracy today. The results of the study show that, although there are obstacles in the implementation of Pancasila principles, the reform era offers great opportunities to strengthen the legal system through the integration of Pancasila values ​​in legislation, strengthening legal institutions, and digitalizing legal processes. With the right strategy, the values ​​of Pancasila democracy can be integrated more effectively into national legal politics, creating an inclusive, just, and sustainable legal system. This research is expected to contribute to the development of legal political theory and become a reference in efforts to strengthen Pancasila democracy as a legal basis in Indonesia.